Pengaruh Work-Life Balance, Self-Efficacy, dan Iklim Organisasi terhadap Employee Engagement pada Guru di Jelai Hulu Kabupaten Ketapang - Wahyudi, Jepan; Pelealu, Deasy Rinayanti (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of work-life balance, self-efficacy, and organizational climate on employee engagement among teachers in Jelai Hulu, Ketapang Regency. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 35 teachers as respondents and analyzed using multiple linear regression analysis. The results showed that work-life balance, self-efficacy, and organizational climate had a positive and significant partial effect on employee engagement. In addition, the simultaneous test results showed that the three independent variables together had a significant effect on employee engagement. The coefficient of determination shows that the research model is able to explain 44.3% of the variation in employee engagement, while the rest is influenced by other factors outside the research model. These findings indicate that improving work-life balance, self-efficacy, and a conducive organizational climate are important factors in increasing teacher engagement. This study is expected to contribute theoretically and practically to human resource management in the field of education.